High Intensity Interval Training Leads to Greater Improvements in Acute Heart Rate Recovery and Anaerobic Power as High Volume Low Intensity Training - Stöggl, Thomas L.; Björklund, Glenn (Frontiers in Physiology, 2017)
The purpose of the current study was to explore if training regimes utilizing diverse training intensity distributions result in different responses on neuromuscular status, anaerobic capacity/power and acute heart rate recovery (HRR) in well-trained endurance athletes. Methods: Thirty-six male (n=33) and female (n=3) runners, cyclists, triathletes and cross-country skiers (peak oxygen uptake: (VO2peak): 61.9±8.0 mL∙kg-1∙min-1) were randomly assigned to one of three groups (high intensity block training HIIT; polarized training POL; high volume low intensity oriented control group HVLIT/CG applying no HIIT). A maximal anaerobic running/cycling test (MART/MACT) was performed prior to and following a nine-week training period. Results: Only the HIIT group achieved improvements in peak power/velocity (+6.4%, P<0.001) and peak lactate (P=0.001) during the MART/MACT, while, unexpectedly, in none of the groups the performance at the established lactate concentrations (4, 6, 10 mmol∙L-1) was changed (P>0.05). Acute HRR was improved in HIIT (11.2%, P<0.001) and POL (7.9%, P=0.011) with no change in the HVLIT oriented control group. Conclusion: Only a training regime that includes a significant amount of HIIT improves the neuromuscular status, anaerobic power and the acute HRR in well-trained endurance athletes. A training regime that followed more a low and moderate intensity oriented model (HVLIT/CG) had no effect on any performance or HRR outcomes.